Bank CEO emotional bias and incentive systems: structural equations model. (2016) - Souissi, Yasmine; Azouzi, Mohamed Ali; Jarboui, Anis
In the present work, an intra-organisational analysis has been undertaken with reference organisational architecture theory, for the purpose of investigating a major loan-granting decision governing mechanism, namely, the incentive system. The paper is primarily axed around highlighting the bank CEO emotional biases' critical impact on explaining the banks' adopted incentive systems, as applied to motivate lower-rank managers, particularly account managers, who are in direct contact with client companies. Our analysis of responses, as drawn from a questionnaire sent to a number of Tunisian bank CEOs, proves to reveal well that the bank CEO's opting for incentive mechanisms specifically reserved to the account manager, turns out to be highly devoted to his proper skillful evaluation (optimism and overconfidence) and a matter of his particular perception of the possible relevant risk (loss aversion).